DEVELOPING ENGLISH READING MATERIALS FOR STUDENTS AT SMK PANCA BUDI 2 MEDAN - Sri Lestari Setiawan; Busmin Gurning (Universitas Negeri Medan, 2016)
This study aims to design English reading materials needed for students atSMK Panca Budi 2 Medan and develop English reading materials for students atSMK Panca Budi 2 Medan. The research was conducted by Research andDevelopment (R & D) design through six phases; gathering information and data,analyzing data, designing new materials, validating by experts, revising, and finalproduct. It was conducted at SMK Panca Budi 2 Medan, especially grade XII. Thedata were gathered by administering interview to English teacher and distributingquestionnaire to 30 students to get the students’ needs. The interview andquestionnaire results prove that the students need English reading materials whichcontain the appropriate knowledge or topic with the BSNP (Badan Standar NasionalPendidikan), syllabus, and students’ level. Thus, developing materials are proceduretext. The procedure texts expose the texts about clerical duties which are adjacentwith students’ life. There are 3 text provided, they are: Arranging a Business Trip,How to Document Petty Cash Slips and Arranging a Formal Meeting. The productshave been validated by experts. The average scores are 4,25 from English teacher and4,25 English lecturer. It means the developing materials categorized as relevant orappropriate for students at SMK Panca Budi 2 Medan grade XII.